2009
DOI: 10.1590/s0103-84782009000700030
|View full text |Cite
|
Sign up to set email alerts
|

Análise morfométrica da parede intestinal e dinâmica de mucinas secretadas no íleo de frangos infectados por Toxoplasma gondii

Abstract: Análise morfométrica da parede intestinal e dinâmica de mucinas secretadas no íleo de frangos infectados por Toxoplasma gondii

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
1
8
0
3
Order By: Relevance
“…Thus, it is suggested that the increase of these birds' secretion of mucin neutral would thicker the mucous covering the epithelium, protecting it from abrasion, what usually occurs during diarrhea. Similar result has also been observed when the ileum of birds in this study was assessed through the technique of detection of glycoconjugates (Shiraishi 2008). Studies on experimental infection with T. gondii demonstrated that the sporozoites cross the intestinal mucosa either through the enterocytes or the caliciform cells (Speer & Dubey 1998).…”
Section: Discussionsupporting
confidence: 85%
“…Thus, it is suggested that the increase of these birds' secretion of mucin neutral would thicker the mucous covering the epithelium, protecting it from abrasion, what usually occurs during diarrhea. Similar result has also been observed when the ileum of birds in this study was assessed through the technique of detection of glycoconjugates (Shiraishi 2008). Studies on experimental infection with T. gondii demonstrated that the sporozoites cross the intestinal mucosa either through the enterocytes or the caliciform cells (Speer & Dubey 1998).…”
Section: Discussionsupporting
confidence: 85%
“…When T. gondii crosses the gastrointestinal tract wall it can cause multifunctional alterations [31][32][33] . These alterations seem to be related to several factors such as genotype strain, life form and inoculation route (oral or intraperitoneal) of the parasite in addition to the infection phase (acute or chronic), digestive tract region and the type of cells assessed [5][6][7][8][9][10][11][12][13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Despite the many studies in literature on intestinal morphometry, most do not clearly describe the methodology applied. Relevant data, such as the evaluated intestinal segment, the time between death and sample fixation, how the segments are sectioned, and criteria to measure the microstructures, are not informed (Alvarenga et al, 2004;Fukayama et al;, Okamoto et al, 2009and Shiraishi et al, 2009. On the other hand, Caruso & Demonte (2005), studying the histomorphometry of the small intestine of rats, describe the details of the methodology applied and of the measurement criteria used.…”
Section: Introductionmentioning
confidence: 99%